Economic value of animal deseases prevention in Costa Rica - Solórzano Thompson, Johanna (2020)
Industrialized countries can control or reduce the risk of zoonotic diseases through public investment in preventive measures such as control, surveillance and disaster management. Costa Rica has an official veterinary service that fulfills this function and has managed to reduce the prevalence of some diseases of animal origin and zoonotic effect. This research aims to calculate the social economic benefit of disease prevention in animals and their effect on public health in Costa Rica. It was carried out during the 2018 period, through working meetings with private veterinarians and SENASA doctors, doctors in human health, as well as interviews with producers in different farms throughout the country. In addition, secondary sources were used to obtain prevalence statistics. The methodology of avoided costs was applied, and the disbursements that the country avoids in the presence of control and without it were calculated. The data obtained demonstrate an economic benefit of more than 125 billion colones distributed in a composition of 21.9% in animal health and 78.1% in human health. There is an obvious economic impact at the social level, due to the lower prevalence of the disease and therefore the lower need to fight it both in farms, houses, jobs, social security, among others.